Ultrashort pulsed laser ablation of granite for stone conservation. (July 2022) - Brand, Julia; Rode, Andrei V.; Madden, Steve; Wain, Alison; King, Penelope L.; Rapp, Ludovic
Highlights: Defined ablation thresholds of four major minerals of granite for fs-laser pulses. Maximum ablation rate of 0.27 ± 0.03 mm 3 ·(min·W) −1 at a fluence of 8.4 ± 1.0 J·cm −2 . Raman spectra show no structural damage to quartz and feldspar at high fluences. Morphological damage at crater bed observed on biotite above its ablation threshold. Safe fluence advised for cleaning/conservation of granite below 1.0 ± 0.1 J·cm −2 . Abstract: This paper investigates the ultrashort pulsed laser ablation of a high heritage value Australian granite comprising quartz, feldspar (plagioclase and minor potassium-feldspar), and Mg-Fe-bearing minerals (biotite and hornblende). This work is relevant to laser cleaning and texturing of heritage stone surfaces and the preparation and maintenance of granite in other applications. The experiments were undertaken in an ambient lab air environment (23 ± 2 °C and 20–40 % relative humidity) with nitrogen blow, on dry surfaces using 275 fs duration laser pulses at 1029 nm. The ablation behaviour of the different granite minerals was experimentally studied in a fluence range of 1– 17 J·cm −2 in the single shot per spot regime and the ablated surfaces were assessed with a multi-analytical approach including optical and scanning electron microscopy, Raman spectroscopy and optical profilometry. The ablation threshold was established for each different mineral in the stone. Biotite is the most readily ablated, with an ablation threshold of 1.1 ± 0.1 J·cm −2 . It is followed by hornblende at 1.3 ± 0.1 J·cm −2, plagioclase at 1.4 ± 0.1 J·cm −2 and quartz, at 1.6 ± 0.1 J·cm −2, which is the most resistant component mineral. Following the electrostatic laser ablation model, the ablation thresholds were theoretically estimated for each mineral phase and demonstrated to be in reasonable agreement with the experimental results. The highest ablation efficiency of the granite as a whole was determined to occur at a fluence of 8.4 J·cm −2, giving an ablation efficiency of 0.27 ± 0.03 mm 3 ·(min·W) −1 in terms of volume removal. From the experimental data, a maximum laser fluence for conservation cleaning was determined at 1.0 ± 0.1 J·cm −2, at which no discernible change or detrimental effect on the granite was observable. Above this fluence, morphological changes were induced in the stone and higher fluences should therefore be avoided for conservation cleaning.